Pengaruh Tax Planning, Investment Opportunity Set dan Growth Opportunity Terhadap Nilai Perusahaan - Ariyadni, Fenny Tidar; Irawati, Wiwit (ABIS: Accounting and Business Information Systems Journal, 2023)
This study aims to examine and obtain empirical evidence of the effect of tax planning, investment opportunities and growth opportunities on firm value. Sampling using purposive sampling obtained a sample of 9 companies with 45 data. The population in this study are manufacturing companies in the basic and chemical industry sectors which are listed on the Indonesia Stock Exchange during the period 2017 – 2021. The regression model in this study is multiple linear regression analysis. The results of the study show that there is a significant positive influence between the investment opportunity set on firm value, meaning that the higher the investment opportunity set of a company, the higher the tendency of the company to increase firm value in manufacturing companies in the basic industrial and chemical sectors. And the results of the study show that there is no effect of tax planning and growth opportunities on firm value, meaning that the company is not motivated by the value of the company that will be generated but rather towards a smaller tax that must be paid without taking into account the stock price besides that there is a change in the total assets owned by the company in During the research period, economic conditions were unstable, so companies were unable to increase firm value in manufacturing companies in the basic and chemical industries.